Evaluation of energy-efficient retrofits in glazing areas of building envelope and the impact of PCM application on energy performance: A case study in İstanbul and Diyarbakir - Cengiz, Hasan Tunay; Gedik, Guelay Zorer; Korkmaz, Ezgi (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2024)
The building and construction sector accounts for 36% of global energy consumption and 39% of CO2 emissions, contributing to climate change. To mitigate this impact, improvements are needed in the building stock, particularly through energy-efficient retrofits to the existing structures. This study focuses on a residential building in Istanbul and Diyarbakir in Turkey to analyze their behavior and the effects of implemented retrofits on energy efficiency. As climate change leads to increasing temperatures in Turkey, the importance of reducing cooling loads during summers becomes more evident in building retrofits. Therefore, various retrofit methods, such as adding solar shading systems (GK1 & GK2), replacing glass with solar low-e systems (C), and using phase-changing materials (FDM). These retrofit methods have shown promising results in reducing summer cooling loads in both cities. Cost per unit reductions of selected retrofit methods of the study can be seen in Figure A.
Keywords: Energy-efficient retrofit; Building energy; Glazing area interventions; Solar shading; Phase change materials; STRATEGIES; Engineering